Activity and Stability of Electrochemically and Thermally Treated Iridium for the Oxygen Evolution Reaction. Issue 11 (29th July 2016) - Geiger, Simon; Kasian, Olga; Shrestha, Buddha R.; Mingers, Andrea M.; Mayrhofer, Karl J. J.; Cherevko, Serhiy
Abstract : Iridium is the main element in modern catalysts for the oxygen evolution reaction (OER) in proton exchange membrane water electrolyzers (PEMWE), which is predominantly due to its relatively good activity and tolerable stability in harsh PEMWE conditions. Limited abundance of iridium, however, poses limitations on widespread applications of these devices, in particular in the large scale conversion and storage of renewable energy. In this work we investigate if the electrocatalytic performance of iridium can be fine-tuned by thermal treatment of catalysts at different temperatures. The OER activity and the dissolution of two different iridium electrodes, viz. (a) flat metallic iridium surfaces prepared by electron beam physical vapor deposition (EBPVD) and (b) electrochemically prepared porous hydrous iridium oxide films (HIROF) are studied. The range of applied annealing temperatures is 100°C–600°C, with a general trend of decreasing activity and increasing stability the higher the temperature. Numerous peculiarities in the trend are however observed. These are discussed considering variations of oxide structure, morphology and electronic conductivity.